Spaces of Belonging: Community Engagement and Social Inclusion in Rural Communities - Hauge, Atle; Calignano, Giuseppe; Winsents, Elisabeth (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale, 2025)
This article explores the crucial role of public spaces and the nonprofit sector in fostering social inclusion within rural communities facing increasing centralization. Challenging purely economic development models, it argues for a holistic understanding of regional wellbeing centred on community engagement in “third places.” By examining the dynamics of space use and the potential for social isolation, the article highlights the importance of human-scale design and strategic revitalization of community-centred spaces to enhance social capital, quality of life, and resilience in smaller urban contexts. It calls for further research into the lived experiences and wellbeing of residents in these areas, advocating for a shift beyond purely economic indicators of local development.